ANALISIS FAKTOR PENENTU EFISIENSI BANK SYARIAH DI INDONESIA DENGAN PENDEKATAN TWO STAGE DATA ENVELOPMENT ANALYSIS (DEA) - OKTAVIANA DWI ANGGRAINI S, ADE; MUSDHOLIFAH (Jurnal Ilmu Manajemen (JIM), 2018)
The result obtained in the first stage that the average of efficiency level of islamic bank during the period of study is 77% (2012), 79% (2013), 78% (2014), 77% (2015), dan 77% (2016), while an Islamic bank efficient during the study period is PT Bank Muamalat Indonesia, PT Bank Syariah Mandiri and PT BPD Jambi. The second stage result study indicates size and FDR have an effect on the efficiency level of the Islamic bank. This should be of particular concern to internal banks in increasing size of bank and FDR ratio by maintaining firm credibility. Thereafter CAR, NPF, ROA, the number of bank branches, and economic growth have no effect on the efficiency level of the Islamic bank. Variable factors of economic growth derived from macroeconomics have no effect on the efficiency level of Islamic bank because of the internal bank able to cope with changes in macro conditions so well that it does not affect the banks operational activities. Keywords : Sharia general bank, Unit of sharia business, Efficiency level, Data Envelopment Analysis, Tobit model.